Taking Midway : naval warfare, secret codes, and the battle that turned the tide of World War II - Dugard, Martin; Dugard, Martin (Dutton, 2025)
"From Martin Dugard, #1 New York Times bestselling coauthor of Bill O'Reilly's Killing series--with more than twelve million copies sold--comes a fast-paced, dramatic account of the famous yet little understood battle that turned the tide of World War II."-- Provided by publisher.